2021
DOI: 10.7759/cureus.19796
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effect of the COVID-19 Pandemic on the Lifestyle of the Population in Saudi Arabia: A Cross-Sectional Online Survey Study

Abstract: Background The coronavirus (COVID-19) pandemic has created an unprecedented problem in people's lives around the world. Lockdown measures altered the routine lifestyle aspects of people including diet, exercise, sleep, stress, smoking, job status, recreation, and application of modern technologies. Understanding the lifestyle profile of individuals could help in designing effective interventions to minimize the risk factors of COVID-19-related health problems. Objectives The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(36 citation statements)
references
References 31 publications
4
32
0
Order By: Relevance
“…The result is similar to those reported in various studies [20,22,30]. Greater awareness of the benefits of proper water intake during quarantine, combined with easy access to water, may have led to this behavior [9].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The result is similar to those reported in various studies [20,22,30]. Greater awareness of the benefits of proper water intake during quarantine, combined with easy access to water, may have led to this behavior [9].…”
Section: Discussionsupporting
confidence: 90%
“…The individuals in Saudi Arabia (SA) experienced extraordinary behavioral changes in all parts of their lifestyle, with some positive effects on smoking and food habits [9]. Unemployment, physical inactivity, sleep difficulties, social isolation, and excessive weight gain were negative changes [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the title and abstract screening stage, 162 records were excluded as irrelevant. After a full-text review of 47 reports, we included 19 studies [ 24 , 31 48 ], all published in English.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…For example, an additional 60 min in daily sedentary time has been reported in adults who strictly followed the COVID-19 guidelines compared with those who did not [ 58 ]. Additionally, recent data showed that screen and social media time significantly increased by 20.5% and 18.7%, respectively [ 59 ]. However, it should be noted that the parents in our study were young (mean age 38.9 years) and 70% were females.…”
Section: Discussionmentioning
confidence: 99%